Factors Influencing HbA1C Values In Patients With Diabetes Mellitus At Mojowarno Christian Hospital - Muhamad Rizal Hadi Pratama; Saski Yasmin Alfina; Christian Dion Saelan (Universitas Nahdlatul Ulama Surabaya, 2026)
Diabetes mellitus (DM) is a metabolic disorder characterized by elevated blood sugar levels. It is a chronic condition that cannot be cured but can be effectively managed. Hemoglobin A1c (HbA1c) measurement is the gold standard for long-term monitoring of blood sugar levels. This study aims to explore the relationship between HbA1c levels and the characteristics of diabetic patients.. The research employed a cross-sectional design at Mojowarno Christian Hospital in Jombang, conducted from November 2023 to January 2024. A total of 72 samples were collected using a purposive sampling technique. Data from questionnaires were analyzed using Spearman's Test and Multiple Logistic Regression Test. The findings indicate that education level, diabetes empowerment, quality of life of patients, and knowledge regarding DM are significantly associated with individual HbA1c values. Among these factors, education emerged as the most influential. Education plays a crucial role in influencing HbA1c levels in individuals with diabetes, highlighting the importance of knowledge and awareness in managing this condition effectively. Keywords: Diabetes mellitus, HbA1C, education